PENATALAKSANAAN FISIOTERAPI DENGAN MODALITAS ULTRASOUND (US) DAN STRETCHING PADA KASUS TRIGGER FINGER DIGITI II MANUS DEXTRA DI RSUD CIBABAT KOTA CIMAHI - Shelly Novianti Ismanda; Diah Ajeng Ningtias Silfa Istihana; Nurul Dwi Ariani (INFOKES (Informasi Kesehatan), 2020)
This research aims to review implementation of physioteraphy with modalities ultrasound (us) and stretching on trigger finger digiti II manus dextra. Research methods that were used is qualitative research was conducted data collection interview technique, and examination patient medical status. The research was conducted in unit of practicing physiotherapist with the total sample 1 people, namely patients trigger the finger digiti II manus dextra that visit into a unit practicing physiotherapist RSUD Cibabat Cimahi at the time did research. The results showed developments with the ultrasound (us) and stretching will help minimize symptoms and complaints felt patients and through 6 (six times therapy) obtained the results of a decrease in pain press on MCP from T1 4,3 became T6 1,1and PIP from T1 3,7became T6 1,1. Motion pain on MCP from T1 5,4 became T6 1,8and PIP from T1 4,1 became T6 1,8. Increase range of motion on MCP from T1 S 0˚- 0˚- 65˚ became T6 S 0˚- 0˚- 75˚ and PIP from T1 S 0˚- 0˚- 55˚ became T6 S 0˚- 0˚- 85˚. It is based on the regular therapy and education given by a therapist to patients and would optimize therapy result given.